LABOR MARKET DEVELOPMENT IN THE REPUBLIC OF UZBEKISTAN: IMPLICATIONS FOR QUALITY - Shakhlo T. Ergasheva; Gulmira Sh. Razikova; Mukaddas A. Umarova; Abbas A. Nabixodjayev; Umida A. Salikhodjaeva (International Journal for Quality Research)
The research aims to define the latest trends in the development of the labor market in the Republic of Uzbekistan and develop recommendations for adapting HRM to these trends to enhance the quality of products of Uzbek organizations. The research was conducted using regression and trend analysis methods based on international statistics for 2023. As a result, the authors identified global regularities of labor market development from the perspective of their consequences for quality. The authors identified trends in the labor market development in the Republic of Uzbekistan in 2023 compared to 2020. The prospects for developing the labor market in the Republic of Uzbekistan were determined. The authors proposed HRM implications for the best scenario implementation in the Republic of Uzbekistan until 2030. The theoretical significance of the results lies in providing a more detailed explanation and elaboration of the contribution of HRM to the growth in the quality of products of contemporary organizations, as well as revealing the unique experience of the Republic of Uzbekistan in improving the quality of products of Uzbek organizations through HRM. The managerial significance of the applied developments of this research lies in the fact that the proposed HRM implications will make it possible to enhance HRM practices in Uzbek organizations.